A Chromosome-Level Genome Assembly of the Dark Sleeper Odontobutis potamophila. (12th February 2021) - Jia, Yongyi; Zheng, Jianbo; Liu, Shili; Li, Fei; Chi, Meili; Cheng, Shun; Gu, Zhimi
Abstract: The dark sleeper, Odontobutis potamophila, is a commercially valuable fish that widely distributed in China and Southeast Asia countries. The phenomenon of sexual dimorphism in growth is conspicuous, which the males grow substantially larger and faster than the females. However, the high-quality genome resources for gaining insight into sex-determining mechanisms to develop sex-control breeding are still lacking. Here, a chromosomal-level genome assembly of O. potamophila was generated from a combination of Illumina reads, 10× Genomics sequencing, and Hi-C chromatin interaction sequencing. The assembled genome was 1, 134.62 Mb with a contig N50 of 22.25 Mb and a scaffold N50 of 24.85 Mb, representing 94.4% completeness (Benchmarking Universal Single-Copy Orthologs). Using Hi-C data, 96.49% of the total contig bases were anchored to the 22 chromosomes, with a contig N50 of 22.25 Mb and a scaffold N50 of 47.68 Mb. Approximately 54.18% of the genome were identified as repetitive elements, and 23, 923 protein-coding genes were annotated in the genome. The assembled genome can be used as a valuable resource for molecular breeding and functional studies of O. potamophila in the future.